Do Natural Resources Affect Unemployment? Evidence from Indonesian Province Panel Data - Gunawan, Beni Teguh (Signifikan: Jurnal Ilmu Ekonomi, 2023)
Since the stipulation of regional autonomy in the early 2000s, local governments have managed their revenues and expenditures independently, in direct or revenue-sharing funds from the Central Government, including income from natural resource exploitation. This study aims to identify the region with high natural resources, especially from the mining and quarrying sectors, expected to improve its human resources quality, focusing on the employment sector. In addition, this study identifies the impact of natural resources on reducing unemployment in 34 provinces in 2015-2021. A previous study implemented natural resources rent to proxy natural resources in a region. However, identification of this proxy has been challenging due to the considerable informality in Indonesia. This study employs mining and quarrying sectors to proxy natural resources as a comprehensive output of a region. The data used in this study was secondary data sourced from the National Statistics Board (BPS). The analysis method of this study was fixed effect with the Human Development Index (HDI) and the unemployment rate as the dependent variable. The results of this study revealed that regional natural resources did not impact HDI or reduce the unemployment rate in a province, indicating that the mining and quarrying sectors did not contribute to improving the quality of human resources and reducing unemployment significantly.JEL Classification: C01, O13, O15, O17How to Cite:Gunawan, B. T (2023). Do Natural Resources Affect Unemployment? Evidence From Indonesian Province Panel Data. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 231-244. https://doi.org/10.15408/sjie.v12i2.31824